Keterampilan komunikasi untuk meningkatkan kemampuan pemecahan masalah pola bilangan - Muljo, Ariyani (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2022)
Problem-solving is a high-level mental process and requires a more complex thinking process. So special treatment is needed so that students can solve the problems given by the teacher. This study aims to explore problem-solving ability through students' communication skills in solving the flat building test. Data were collected through written tests on number pattern problems and interviews for anything unclear. The data were analyzed by the constant comparative method. The research was conducted on 30 students of Nurul Huda Junior High School in Malang. The result of the research is the stages of problem-solving through communication skills in solving math problems namely: understanding the problem, planning the solution, implementing the plan, and looking back. Our findings show that communication skills have an important role in the researcher's exploration of building students' problem-solving abilities. Students who are able to communicate well orally and in writing can solve problem-solving tests/questions and are interested in facing challenges and willingness to solve problems. The results and findings of this study can contribute knowledge to educators in building students' problem-solving abilities through their communication skills throughout problem-solving.